Psalm 1 jako zachęta do czytania i studiowania Pisma Świętego - Knut, Tadeusz (Collectanea Theologica, 2016)
The sapiential Psalm 1 contains a teaching on the two paths of the human life and the consequences of our choices. It contrasts the just man who is “happy” (v. 1) with the villains who are “lost” (v. 6). According to the psalmist the man is fulfilled when he radically avoids the ways of the wicked and “delights in the Divine Precepts” which they “meditate tirelessly” (v. 2). The notion of the Law refers here to the books of the Bible – that is the written Word of God which the lives of the just are imbibed in and which serves as the moral compass. God, in response to such a devoted attitude, watches over the life of the righteous and provides for his needs. Psalm 1 serves as an encouragement to read the Bible and to meditate upon the will of God which is found on its pages. This is the way to achieve the ultimate happiness which the man can be experienced in the intimate union with God both on Earth and in the World to come.